Pharmacy students' perception and inclination toward scholarly research publications: A multinational study - Akshaya Srikanth Bhagavathula; Deepak Kumar Bandari; Shazia Qasim Jamshed; Vijay Kumar Chattu (Wolters Kluwer Medknow Publications, 2018)
BACKGROUND: Scholarly research experiences during student life can make pharmacy students capable of reaching the pinnacle of triumph with scientific skills. AIM: The aim of this study is to assess the perception of pharmacy students and their inclination toward scholarly research publications. MATERIALS AND METHODS: A cross-sectional web-based survey was conducted among pharmacy students across India, Malaysia, and Pakistan. A 21-item questionnaire was distributed through different social networking sites between July and September 2016. Descriptive and Chi-square tests were used to analyze the findings. A value of P < 0.05 was considered as statistically significant. RESULTS: Of 543 pharmacy students approached, 348 participants from India, Pakistan, and Malaysia were included giving a response rate of 64%. The study comprises 48.5% of males and 51.4% of females, studying a bachelor of pharmacy (44.5%), and from private institutions (94%). Nearly, three-fourths (76.4%) of the students had no publications but showed high interest toward original research (87.4%). Most of the participants cited the reasons to engage in the scholarly publication is too advanced research/share findings (74.1%), and to improve writing and research skills (73.6%). Further, a significant percentage of students agreed that contributing to the literature during student life as a valuable experience and publishing will provide them with personal fulfilment. CONCLUSIONS: This study showed that most of the pharmacy students had positive perceptions toward scholarly research activities to advance research and improve their writing research skills. We recommend the pharmacy schools to incorporate scholarly activities in the curriculum to embark research-inclusive career.